On the Stock Markets' Reactions to Taxation and Public Expenditure - Pasquale Foresti; Oreste Napolitano (London School of Economics and Political Science (LSE), European Institute, 2016)
In this paper a panel analysis is employed to investigate the effects of governments' expenditure and taxation on stock market indexes in 11 members of the Eurozone. A significant number of studies have focused on the effects of monetary policy on the Eurozone stock markets, while only a limited number of papers have investigated the effects of fiscal policy on the stock markets. Therefore, we know little, if anything, on the sign and the stability of the stock markets' reaction to taxation and public expenditure. Our results show that fiscal maneuvers influence stock markets and that, following an increase (decrease) in public deficit, stock markets indexes go down (up). Nevertheless, further analysis shows that the signs of the estimated stock markets' reactions are not constant over time and that they can change according to the surrounding macroeconomic scenario.
Keywords: 330; Stock Market; Fiscal Policy; Eurozone